2015
DOI: 10.1007/s12639-015-0683-z
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Enterobius vermicularis amongst kindergartens and preschool children in Mazandaran Province, North of Iran

Abstract: Enterobiasis (oxyuriasis) is probably the most common helminth, which infects humans. Amongst different age groups, prevalence of Enterobius vermicularis in children is high compared to adults. Oxyuriasis is one of the most significant parasitic diseases of children. This nematode in children can result in loss of appetite, insomnia, grinding of the teeth, restlessness, endometritis, abdominal cramps, diarrhea and etc. Due to important complications of this parasite, the objective of the current study was to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 13 publications
2
24
2
1
Order By: Relevance
“…In the backwards citation tracking process, three relevant papers were added. In the final step, inclusion/exclusion criteria were applied and the rest of the papers were quality assessed; after that point, 19 studies [1012,17–32] were entered into the final meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the backwards citation tracking process, three relevant papers were added. In the final step, inclusion/exclusion criteria were applied and the rest of the papers were quality assessed; after that point, 19 studies [1012,17–32] were entered into the final meta-analysis (Figure 1). …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, two studies assessed the association between infection and bruxism [10,18], while another study reported the association of E. vermicularis with family size, anal itching, nail biting, familial history of E. vermicularis , and personal history of other parasitic infections were not significant.…”
Section: Resultsmentioning
confidence: 99%
“…According to literature review many efforts have been conducted in different areas of Iran including Alborz, Isfahan, Urmia, Amol, Sari and Babol, Semnan, Kermanshah, Ardebil, Zahedan, Babol, Ahwaz and Tehran were 0. 028, 2.38, 4.6, 7.1, 7.3, 8.1, 14.7, 18.3, 31.8, 33.3, 34.6 and 40 %, respectively (Nourozian and Youssefi 2013;Sharifi and Abd 2000;Sha-Mohammadi et al 2014;Maraghi 1997;Daryani et al 2003;Afrakhteh et al 2015). The prevalence of E. vermicularis amongst children has been reported in many parts of the globe, and varies considerably, depending on the age groups and areas (WHO 1998;Kang et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Usually, children are considered as the main targets, because of this fact that children's behaviors contribute more to the development of E. vermicularis infection compared to adults (Afrakhteh et al 2015). Some important factors may increases risk of acquiring enterobiasis in children including being in overcrowded places, playing on the floor, nail biting, failure to wash hands before meals and living in non-apartment dwellings.…”
Section: Discussionmentioning
confidence: 99%
“…Kejadian enterobiasis masih relative tinggi di berbagai penjuru dunia, diantaranya pada anak sekolah di Yangon Myanmar sebesar 47,2 % [1]. Di Iran memiliki angka yang bervariasi, anak pra sekolah di Babol Iran yang mengalami enterobiasis sebesar 22,2 % [2], sedangkan di daerah Mazandaran Iran hanya sebesar 7,1 % [3]. Di kota Xinxiang provinsi Henan, China telah terjadi penurunan kasus enterobiasis dimana pada tahun 2003 tercatat sebanyak 12,75 % dan pada tahun 2013 turun menjadi 5,13 % [4].…”
Section: Pendahuluanunclassified